Impact of Vgsc-1014 mutations on the feeding pattern of Phlebotomus argentipes - Bruno Gomes; Debashis Ghosh; Rajib Chowdhury; M. Mamun Huda; Abdul Alim; Mark Paine; Dinesh Mondal; David Weetman (PLoS ONE, 2025)
Knockdown resistance alleles (kdr alleles) within the para voltage-gated sodium channel gene (Vgsc) are a common mechanism of DDT and pyrethroid resistance in insect vectors. In the primary Asian visceral leishmaniasis vector, Phlebotomus argentipes, two kdr alleles in codon 1014 of the Vgsc are associated with insecticide resistance, potentially presenting challenges to vector control efforts in the Indian subcontinent. Here, we screened Vgsc-1014 alleles and blood meal origin in P. argentipes females collected between September 2013 and August 2015 in Bangladesh (Mymensingh), to understand how Vgsc-1014 alleles could impact feeding patterns. The sand fly collection took place in parallel with the vector control agency’s biannual indoor residual spraying (IRS) programme. In this region, the wild-type leucine (wt-leucine) was the most common allele (66.7%), followed by the mutant serine (19.4%) and phenylalanine alleles (13.9%). Only 55 sand fly blood meals (13%) came from humans, with most of bovine origin (61%). However, sand flies that had fed on humans showed strongly contrasting Vgsc-1014 genotypic frequencies compared to those feeding on other blood sources. Whilst most (81%) P. argentipes with human blood possessed kdr genotypes with two mutant alleles, most (81%) sand flies feeding on other blood sources possessed genotypes with wt-leucine alleles (P < 0.001). Significant spatial variation in kdr frequencies was detected, but there was no clear temporal trend nor effect of sampling year on any results, and no significant impact of recent IRS in any analyses. The association between human feeding and kdr alleles in parallel with pyrethroid spraying indicates a new mechanism of how kdr alleles might impact VL control programs.